Nab-paclitaxel and trastuzumab combination: a promising approach for neoadjuvant treatment in HER2-positive breast cancer - Ricciardi, Giuseppina Rosaria Rita (Onco Targets Ther, 2016)
Neoadjuvant therapy is a well-established approach for the treatment of locally advanced or inflammatory breast cancer (BC) and has been increasingly used in recent years not only as a management strategy but also as a research tool. Recently, nanoparticle albumin-bound paclitaxel (nab-paclitaxel)/trastuzumab combinations have been associated with promising activity in different clinical settings. In the present case, we report a complete pathological response after neoadjuvant treatment with the trastuzumab/nab-paclitaxel combination in a locally advanced human epidermal growth factor receptor 2 (HER2)-positive BC patient, with a good toxicity profile. This combination may represent a valid therapeutic option in the neoadjuvant therapy for HER2-positive locally advanced BC.